Measuring learning enablers in the Malaysian Armed Forces: pre-testing and pilot testing of the research / Mohd Roziman Zainal and Mohamad Noorman Masrek - Zainal, Mohd Roziman; Masrek, Mohamad Noorman (Faculty of Information Management, 2023)
This paper reports the findings of a study aimed at addressing learning enablers in the Malaysian Armed Forces. To accomplish this objective, an instrument has been developed. The constructs used to assess learning enablers were derived from the literature review. A total of nine construct were used, namely continuous learning, dialogue and inquiry, team learning, employee empowerment, leadership for learning, system connections and embedded system. A perceptual measures adapted from the literature were developed and pre-tested with eight experts. Their comments and feedback were used to refine the measures. Accordingly, a pilot testing was conducted involving 40 respondents who were military officers. The results of the analysis showed that the measures were acceptably reliable. The findings of this study will be used for a follow-up study that will examine the interrelationship between those constructs.